The Effectiveness of Environmental Law Enforcement in Combating Deforestation in West Papua, Indonesia - Irmayani, I.; Roberth KR Hammar; Bernardus Hirokubun (Golden Ratio of Law and Social Policy Review, 2025)
This research is motivated by the high rate of deforestation in West Papua, which has had a widespread impact on tropical forest ecosystems, biodiversity, and the socio-economic lives of indigenous communities. The urgency of this research lies in the need for an in-depth evaluation of the effectiveness of regulations and law enforcement systems in preventing and mitigating deforestation. This study uses a qualitative approach with an empirical juridical research style. Data collection techniques were conducted through literature studies, documentation, and interviews with various stakeholders, such as academics, environmental activists, and regional officials. Data were analyzed using descriptive analytical methods with normative and sociological approaches. The results of the study reveal two main findings. First, the impacts and efforts to prevent deforestation in West Papua include ecosystem damage, biodiversity loss, indigenous peoples' rights disruption, and contributions to the climate crisis and agrarian conflicts. Although forest protection regulations, a moratorium on new permits, and a reforestation program have been in place, their implementation remains weak due to limited oversight, low community participation, and a lack of enforcement of violations. Second, the effectiveness of environmental law enforcement is still less than optimal. Enforcement is still dominated by administrative rather than criminal approaches, with weak institutional capacity and political-corporate intervention hampering the independence of law enforcement. There is a clear gap between legal norms and practices in the field, indicating the need for structural and cultural strengthening in the environmental legal system in West Papua.